1993
DOI: 10.1016/0042-6989(93)90099-i
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropies in the perception of stereoscopic surfaces: The role of orientation disparity

Abstract: We measured stereoscopic slant detection thresholds for surfaces slanting about a horizuntai or a vertical axis. For randomdot covered s&aces, 1.25deg uf slant was required to detect slant about a ants axis, whereas 2.1 deg of slant was required tu detect sbmt abut 8 wrtic8l mds. T&3 8nisOtrOpy could be due t0 the fact th8t Orieltt8tiOO 4#k!iptitiwt Which ~311tim kki~8tiOn about mrf8ce slant, are generally smaller for surfaces slsnting about 8 verticad 8xis. To test this possibility, slant threshuids were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 24 publications
5
47
1
Order By: Relevance
“…However, these data have never been published in a peer-reviewed journal, and to our knowledge, the effect has not been replicated. Psychophysical studies of orientation disparity have had conflicting interpretations (Gillam & Rogers, 1991;Gillam & Ryan, 1992;Cagenello & Rogers, 1993;Heeley, Scott-Brown, Reid, & Maitland, 2003). In general, these studies have found evidence that humans can perceive slant from binocular images related by geometric distortions that are consistent with orientation disparity and that sensitivity to slanted surfaces depends on the orientations of the texture elements.…”
Section: Introductionmentioning
confidence: 95%
“…However, these data have never been published in a peer-reviewed journal, and to our knowledge, the effect has not been replicated. Psychophysical studies of orientation disparity have had conflicting interpretations (Gillam & Rogers, 1991;Gillam & Ryan, 1992;Cagenello & Rogers, 1993;Heeley, Scott-Brown, Reid, & Maitland, 2003). In general, these studies have found evidence that humans can perceive slant from binocular images related by geometric distortions that are consistent with orientation disparity and that sensitivity to slanted surfaces depends on the orientations of the texture elements.…”
Section: Introductionmentioning
confidence: 95%
“…10). Although it has been suggested that such orientation differences might be a specialization for detecting surface slant (Blakemore et al, 1972;von der Heydt, 1978;Ninio, 1985;Mitchison and McKee, 1990;Cagenello and Rogers, 1993), within the context of the energy model, the response remains dominated by the effects of positional disparity , their Fig. 7), so that the modulation at low frequencies is very similar to that at intermediate frequencies.…”
Section: Comparisons Of the Physiological Data With Predictions From mentioning
confidence: 99%
“…The perception of inclination was faster. This difference in performance between the two orientations is one aspect of the so called stereoscopic anisotropy, which is also manifest in terms of differences in threshold performance and differences in the magnitude of perceived depth, despite the fact that the magnitudes of the positional disparities are the same in each case (e.g., Bradshaw & Rogers, 1999;Cagenello & Rogers, 1993;Gillam & Rogers, 1991;Mitchison & McKee, 1990;Parton, Bradshaw, Davies, & Rogers, 1996;Rogers & Graham, 1983).…”
Section: Slanted Planar Surfaces: the Stereoscopic Anisotropymentioning
confidence: 99%